Speed Harmonic Based Saturation Free Inductance Modeling and Estimation of Interior PMSM Using Measurements Under One Load Condition - Guodong Feng; Yuting Lu; Zhe Tong; Beichen Ding; Guishan Yan; Chunyan Lai (CES Transactions on Electrical Machines and Systems)
For permanent magnet synchronous machines (PMSMs), accurate inductance is critical for control design and condition monitoring. Owing to magnetic saturation, existing methods require nonlinear saturation model and measurements from multiple load/current conditions, and the estimation is relying on the accuracy of saturation model and other machine parameters in the model. Speed harmonic produced by harmonic currents is inductance-dependent, and thus this paper explores the use of magnitude and phase angle of the speed harmonic for accurate inductance estimation. Two estimation models are built based on either the magnitude or phase angle, and the inductances can be from d-axis voltage and the magnitude or phase angle, in which the filter influence in harmonic extraction is considered to ensure the estimation performance. The inductances can be estimated from the measurements under one load condition, which is free of saturation model. Moreover, the inductance estimation is robust to the change of other machine parameters. The proposed approach can effectively improve estimation accuracy especially under the condition with low current magnitude. Experiments and comparisons are conducted on a test PMSM to validate the proposed approach.